Karst sediments in Slovenia: Plio-Quaternary multi-proxy records. (30th April 2020) - Zupan Hajna, Nadja; Bosák, Pavel; Pruner, Petr; Mihevc, Andrej; Hercman, Helena; Horáček, Ivan
Abstract: We synthesize information on results and age of cave sediments from Slovenia. The studied sites were mostly from the Classical Karst which is situated in the NW part of Dinarides and some from the Slovenian Southern Alps. Protected in caves, sediments are generally well preserved and reveal an exceptionally good, multi-proxy record of surface environmental conditions at the time of their deposition. Here we describe results of the systematic acquisition of palaeomagnetic data within individual segments of studied sediment sections with special focus on relict and unroofed caves. In intervals with polarity change, the frequency of sampling was so high that almost continuous records of rockmagnetic and palaeomagnetic parameters were obtained. The construction of high-resolution magnetostratigraphic profile supported magnetostratigraphy correlations among profiles. Palaeomagnetic and magnetostratigraphy results were calibrated by relative, numerical, calibrated and correlated dating methods, where possible. Age sequences were compiled from spatially and temporally highly discontinuous sediment records covering different ages within the Cenozoic era. The robust chronology was constructed. Calibrated data contributed to the interpretation of speleogenesis, deposition mechanism in caves, and indirectly to the time of karst evolution and the succession of tectonic phases and climate changes. The research indicated that most of sediments in relict and unroofed caves are up to 5 Ma old which contrasts to the traditional concept of Pleistocene age of cave sediments and that caves themselves are not much older. Cave sediments have proven to be an important source of information on depositional style in caves which indirectly reflected the evolution of the surrounding landscape especially the evolution of catchment areas – i.e. climatic changes with flood events or/and changes of the tectonic regimes during Cenozoic.